2022
DOI: 10.3390/ijms231911422
|View full text |Cite
|
Sign up to set email alerts
|

Functional Plasmon-Activated Water Increases Akkermansia muciniphila Abundance in Gut Microbiota to Ameliorate Inflammatory Bowel Disease

Abstract: Inflammatory bowel disease (IBD) is associated with dysbiosis and intestinal barrier dysfunction, as indicated by epithelial hyperpermeability and high levels of mucosal-associated bacteria. Changes in gut microbiota may be correlated with IBD pathogenesis. Additionally, microbe-based treatments could mitigate clinical IBD symptoms. Plasmon-activated water (PAW) is known to have an anti-inflammatory potential. In this work, we studied the association between the anti-inflammatory ability of PAW and intestinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…The innovation of PAW was considered novel, but its application against diseases or benefits to the regulation of physiological functions remains unknown. A previous study demonstrated that the consumption of PAW replacing drinking water had anti-inflammatory effects and could be beneficial to the relative abundance of specific probiotics such as Akkermansia muciniphila and other butyrate-producing bacteria in mice with colitis induced by 2,4,6-trinitrobenzenesulfonic acid [54]. Additionally, the combination of cisplatin and PAW in drinking water extended survival time in lung cancer mice-implanted LCC-1 cells compared to the combination of cisplatin and deionized water, and the possible mechanisms could be associated with the anti-inflammatory and antioxidant properties of PAW, which was proven by inducing nuclear factor erythroid 2-related factor 2 (Nrf2) antioxidant gene in human gingival fibroblasts [18].…”
Section: Discussionmentioning
confidence: 99%
“…The innovation of PAW was considered novel, but its application against diseases or benefits to the regulation of physiological functions remains unknown. A previous study demonstrated that the consumption of PAW replacing drinking water had anti-inflammatory effects and could be beneficial to the relative abundance of specific probiotics such as Akkermansia muciniphila and other butyrate-producing bacteria in mice with colitis induced by 2,4,6-trinitrobenzenesulfonic acid [54]. Additionally, the combination of cisplatin and PAW in drinking water extended survival time in lung cancer mice-implanted LCC-1 cells compared to the combination of cisplatin and deionized water, and the possible mechanisms could be associated with the anti-inflammatory and antioxidant properties of PAW, which was proven by inducing nuclear factor erythroid 2-related factor 2 (Nrf2) antioxidant gene in human gingival fibroblasts [18].…”
Section: Discussionmentioning
confidence: 99%
“…Akkermansia Muciniphila is a Gram-negative bacterium belonging to Verrucomicrobia phylum. It colonizes the mucosal layer of the gastrointestinal tract by interfering with the metabolism of mucin, which is necessary for the maintenance of the homeostasis of the intestinal wall [99,100]. Macchione et al, observed that a reduction in A. muciniphila correlates with a range of gastrointestinal disorders, including IBD [100][101][102].…”
Section: Akkermansiamentioning
confidence: 99%
“…Akkermansia Muciniphila is a Gram-negative bacterium belonging to Verrucomicrobia phylum. It colonizes the mucosal layer of the gastrointestinal tract by interfering with the metabolism of mucin, which is necessary for the maintenance of the homeostasis of the intestinal wall [ 99 , 100 ].…”
Section: Microbiotamentioning
confidence: 99%